FRI0234 Complement depletion in rheumatoid arthritis patients treated with tocilizumab: a marker of clinical efficacy?. (23rd January 2014) - Sandri, G.; Lumetti, F.; Ferri, C.; Mascia, M. T.
Abstract : Objectives: Tocilizumab (TCZ) is a humanized monoclonal antibody against the α-chain of the IL6 receptor. In clinical trials TCZ had been shown to lower complement levels in Rheumatoid Arthritis (RA) patients independently of disease activity. We therefore evaluated complement factors in our series of patients treated with anti IL6 to show whether there was any correlation. Methods: 16 patients with active RA (14 F/2 M; mean age 56.3±11.2SD) were treated with TCZ (13 after anti-TNF failure and 3 naives). The patients were monitored for therapy response (DAS 28), HAQ, including clinical and laboratory parameters. All patients received DMARDs treatment and prednisolone ≤ 7.5 mg/day. Results: Prior to the treatment, therapy complement levels were normal: C3 124.65±14.52 and C4 23.88±7.23 (normal values: C3 90-180 mg/dl, C4 10-40 mg/dl). Revaluation of these parameters revealed a decrease already after the first 3-month treatment. The complement depletion increased at the 6 th month and persisted during the ongoing therapy. After the 12 th month mean values were C3 89.35±10.21 and C4 11.64±6.39. In four patients the treatment was stopped for the clinical remission with normalization of C3/C4 factors in the follow-up. Concerning the RA disease activity, 14/16 patients showed a good EULAR response (initial DAS28: 5.79±0.86, ESR 41.94±18.81, CRP 3.62±3.14, HAQ 1.39±0.71; after 3 months DAS 28 2.23±0.52, ESR 6.13±3.10, CRP 0.27±0.24, HAQ 0.79±0.73). After 24 weeks, for 2/16 patients (1F/1M) the therapy was stopped for inefficacy; in both patients the levels of complement factors did not decrease during TCZ treatment. In all patients no signs for the development of autoimmunity or infection could be observed. Conclusions: In the Tocilizumab OPTION study, mean levels of complement proteins C3 and C4 decreased but the data were not shown. It can be hypothesized that complement factors are consumed during the elimination process of immune complexes (IL6-anti-IL6Ab); moreover, in a case report of six RA patients the authors commented that this phenomenon requires further observation with respect to the clinical relevance. In an open label, dose-escalating, Phase I study Tocilizumab in Systemic Lupus Erythematosus complement C3 and C4 showed clear dose-related decreases. The Authors of such trial provided the first evidence that the TCZ-associated hypocomplementemia represents decreased production rather than increased activation. Also Olokizumab, a novel IL6 inhibitor in trials showed in RA patients the same dose-related reductions in complement C3 and C4. Reduction in complement levels is therefore believed to be consecutive to the inhibition by TCZ of IL6 stimulation of hepatocyte acute phase protein synthesis and of significant C3 upregulation. In our patients there is a good correlation between C3 and C4 decrease and clinical response, while we have not observed any decrease in patients unresponsive to TCZ. The levels of C3 and C4 are more related to the efficacy than PCR or ESR values, which in 1 patient decreased in absence of clear clinical improvement. The number of patients is too small to reach a conclusion but we hypothesize that the dosage of the C3 and C4 can be a rapid and sensitive marker of the response to anti-IL6 treatment. Therefore, a close follow-up of these parameters at 2-3 months from the start of the therapy can guide the therapeutic strategy. Disclosure of Interest : None Declared